LANGUAGE GAME TECHNIQUES IN THE PROCESS OF LEARNING WORD FORMATION AT SCHOOL AND UNIVERSITY - Muslimova Rano Muratovna (Journals Park Publishing, 2025)
The article discusses the principles and possibilities of introducing gaming training technologies into the practice of school and university education. The subject of the study is the formation and development of the word-formation component of the language competence of the individual, which involves addressing some important issues in the development of the derivational process by students. The problem of transferring formal linguistic knowledge to the mode of pragmatic-operational use is discussed. The idea is postulated that the sequence of word-creative training is determined by a complex of factors that contribute to the efficiency of the speaker's activity in the process of generation and perception of a derivative word. Such factors include mechanisms, methods, typical algorithms of word creation, the idiom of word-formation innovation, the orientation towards updating the semantics of the word, taking into account its motivational form and meaning, the ability to express the nominative need in a variable way, including in a playful way.
Keywords: Derivation; language game; training; linguistic education.